Facilitators and barriers in managing older chronic heart failure patients in community health care centers: a qualitative study of medical personnel's perspectives using the socio-ecological model - Lou, Yan; Zhang, Min; Zou, Yun; Zhao, Le; Chen, Yangfan; Qiu, Yongzhen (Frontiers in Health Services, 2025)
BackgroundCommunity health care centers (CHCs) plays a crucial role in ensuring timely diagnosis and effective management of congestive chronic heart failure (CHF) in older patients. Understanding the current status of CHF management in CHCs can therefore be effective in reducing the disease burden of CHF.ObjectivesThis study evaluates the current state of CHF services in community healthcare facilities and identifies key facilitators and obstacles faced by medical personnel in China.MethodsThis interpretive study applied the social ecological model (SEM) and used a semi-structured interview guide for data collection. Each interview lasted 45–60 min. Thematic analysis was used to analyze the data.ResultsThis study involved 30 participants. Facilitators and barriers were identified within the five domains of the SEM. (1) Individual level: medical staff lack knowledge and experience in CHF management while patients' need for greater health education. (2) Interpersonal level: insufficient support from the patients' family and lack of trust in CHCs and staff. (3) Organizational level: inadequate medical knowledge and training programs for medical staff, shortage of medical staff and limited teamwork and few health promotion channels. (4) Community level: Lack of regular screening and follow-up, medical equipment and an information technology-assisted monitoring system. (5) Public policy level: lack of policy support, funding subsidies, national guidelines adapted to the local context and low medical insurance reimbursement rate.ConclusionThere are many impediments to chronic disease management in the community, so it is vital to improve public understanding of CHF, as well as to improve the quality of community health equipment and services, to improve reciprocal referral mechanisms between hospitals and the community, and to develop policies on chronic disease management for CHF.